2022
DOI: 10.3390/en15041384
|View full text |Cite
|
Sign up to set email alerts
|

The Social Acceptance of Airborne Wind Energy: A Literature Review

Abstract: Airborne wind energy (AWE) systems use tethered flying devices to harvest higher-altitude winds to produce electricity. For the success of the technology, it is crucial to understand how people perceive and respond to it. If concerns about the technology are not taken seriously, it could delay or prevent implementation, resulting in increased costs for project developers and a lower contribution to renewable energy targets. This literature review assessed the current state of knowledge on the social acceptance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…A review of the technology and the different concepts can be found in [4][5][6]. This paper was based on the widely adopted concept of converting the pulling force on the ground using a drum-generator module.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the technology and the different concepts can be found in [4][5][6]. This paper was based on the widely adopted concept of converting the pulling force on the ground using a drum-generator module.…”
Section: Introductionmentioning
confidence: 99%
“…Heavier fixed-wing kites fly faster, and a crash landing typically amounts to a total loss of the kite. Another important aspect next to the availability and maintenance cost is the safety of persons, properties, and critical infrastructures on the ground and other airspace users [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various conceptual differences, the consensus in the industry is that safe and robust operation with a sufficient degree of autonomy is an important prerequisite for a successful market introduction of AWES and acceptance by the public [8,9]. To our knowledge, this target has not yet been achieved, as none of the commercial prototypes have been operated continuously for more than a few days.…”
Section: Introductionmentioning
confidence: 99%
“…Typical challenges when designing and operating AWE systems include the added complexity and dependence on a robust and reliable control system [3] as well as high-performance materials. Furthermore, existing regulations have to be revised to accommodate the operation of high-altitude tethered aircraft for power generation and more research is needed on the social acceptance of AWE systems [4].…”
Section: Introductionmentioning
confidence: 99%